Between the Heroic Cultural Model and A Possible Intelligence Doctrine - Stefanović, Zoran (Napredak, 2023)
The breakup of the ideologically repressive and antinational security apparatus of the Socialist Federal Republic of Yugoslavia created a system directed towards the revival of Serbian statehood in Serbia and Serbian countries in the 1990s. Based on the new monograph book by Karan and Kajtez, this article analyzes the activities of Jovan Milanović, Serbian intelligence officer in Brussels, the NATO headquarters, which protected the Republic Srpska and the Federal Republic of Yugoslavia in the war. By studying personal characteristics, it is concluded that the essence of Serbian strategic culture is primarily related to Serbian cultural codes and ethos, and not only to the implied security, military and geopolitical aspects.